Study of photovoltaic performances for asymmetrical and symmetrical chlorinated thiophene-bridge-based conjugated polymers. Issue 7 (16th January 2020) - Ma, Kangqiao; An, Cunbin; Zhang, Tao; Lv, Qianglong; Zhang, Shaoqing; Zhou, Pengxin; Zhang, Jianqi; Hou, Jianhui
Abstract : Two conjugated polymers with asymmetrical and symmetrical chlorinated thiophene-bridges were synthesized to study their photovoltaic performances. Abstract : Two conjugated donor polymers (PB2F-Cl and PB2F-2Cl ) based on benzo[1, 2- b :4, 5- b ′]dithiophene and benzo[1, 2- c :4, 5- c ′]dithiophene-4, 8-dione with asymmetrical and symmetrical chlorinated thiophene-bridges were designed and synthesized. Both polymers exhibited extremely deep HOMO levels of −5.50 and −5.56 eV for PB2F-Cl and PB2F-2Cl, respectively. Although PB2F-Cl had a more planar conjugated backbone, PB2F-Cl exhibited a weaker aggregation behaviour than PB2F-2Cl in chlorobenzene solution due to its regioirregular conjugated backbone. After blending with an IT-4F acceptor, the PB2F-Cl :IT-4F film exhibited a slightly stronger lamellar stacking and a weaker π stacking compared to the PB2F-2Cl :IT-4F film as confirmed by grazing-incidence wide-angle X-ray scattering (GIWAXS) measurements. In PSCs, the power conversion efficiency (PCE) of the PB2F-C l:IT-4F-based PSC was 10.81%, while the PCE of the PB2F-2Cl :IT-4F-based PSC reached 12.79%.